The Relationship between Job Stress Risk Factors andWorkplace Well-Being with the Moderating Effects of JobBurnout: A Study of Substitute Educators for Early ChildhoodEducation in Taiwan - Kao, Chia-Lin; Chang, Wei-Wen (European Journal of Multidisciplinary Studies, 2022)
Nowadays, the employees’ well-being has been an increasingly relevant andnecessary consideration in the workplace. However, little attention has beenpaid to the well-being of substitute educators in preschool. Working in earlychildhood education is stressful, and certain types of stress negatively affectphysical and mental health. The participants in this study are substituteeducators for early education in Taiwan. The substitute educators ofpreschools in the working environment are not stable and peaceful. Inaddition to engaging in the same teaching programs as the formal teachers,substitute teachers have to work for additional administrative assignments inschools. Furthermore, they were often viewed as the marginal role in theworkplace, enduring discrimination from the unfriendly organization. Theirworking environment is full of pressure, contradictions, and conflicts.Substitute teachers often endure negative emotions and need to suppresstheir true feelings. Thus, the aim of this research is to examine the relationshipamong preschool substitute teachers’ well-being (Y), job stress risk factors(X), and burnout (Mo). Data was collected from a survey of 102 substituteeducators at both public and private preschools in Taiwan. Among the sixstress risk factors, good control, managerial support, colleague support, roles,and change were positively related to well-being, while the other two factors,demand and unfriendly relationship have a negative impact on workplacewell-being. In addition, job burnout has a significant moderating effect on therelationship between job stress risk factor and well-being. Suggestions areprovided for substitute educators’ well-being improvement.
Keywords: job stress risk factors, workplace well-being, job burnout